Registration of three Gossypium barbadense L. American pima‐like germplasm lines (PSSJ‐FRP01, PSSJ‐FRP02, and PSSJ‐FRP03) with improved resistance to Fusarium wilt race 4 and good fiber quality. Issue 3 (28th May 2022) - Ulloa, Mauricio; Abdurakhmonov, Ibrokhim Y.; Hutmacher, Robert; Schramm, TariLee; Shermatov, Shukhrat; Buriev, Zabardast; Roberts, Philip; Ellis, Margaret L.; Payton, Paxton
Abstract: Over the past 18 yr, Fusarium wilt race 4 (FOV4) has affected cotton ( Gossypium spp.) production in the San Joaquin Valley of California, and more recently this pathogen was formally identified in 2017 in the El Paso, TX, region and in 2019 in New Mexico. The primary purpose for the germplasm release is to provide cotton breeders with needed alternative sources for continuing to improve FOV4 resistance in pima cotton. PSSJ‐FRP01 (Reg. no. GP‐1107, PI 699963) (PS‐592) originated from Pima S‐6 × G. barbadense pool accessions GB1368/k‐7616. Pima S‐6 possesses a major gene(s) for FOV4 resistance. GB1368/k‐7616 is Uzbekistan accession introduction with different plant structure, large leaves, columnar growth, and a more clustered fruiting habit when compared to most American pima. PSSJ‐FRP02 (Reg. no. GP‐1108, PI 699964) and PSSJ‐FRP03 (Reg. no. GP‐1109, PI 699965) originated from PS‐592 × SA‐3208 (LIAO MIAN 7 HAO). SA‐3208 is moderately resistant to FOV4. Multiple selections and recurrent cycles of selections were applied to these new germplasm lines based on an asymptomatic single plant after greenhouse FOV4 inoculations and/or infested field evaluations from F1 to F4 . In subsequent field and greenhouse tests in 2019–2021, the germplasm lines showed improved resistance to FOV4 based on low percentage mortality and vascular staining and fiber quality when compared to commercial cultivars. PSSJ‐FRP01, PSSJ‐FRP02, and PSSJ‐FRP03 lines will help to continue reducing the vulnerability of the pima cotton industry to this fungal pathogen and to advance efforts to broaden the genetic base of FOV4 resistance, which is critical to the pima cotton industry in the United States and Uzbekistan. Core Ideas: Alternative germplasm sources are needed to improve FOV4 resistance in pima cotton. Introgression of American pima and Uzbek G. barbadense breeding‐pool material increases diversity. Lines will continue to reduce the vulnerability of the pima industry to FOV4 fungal pathogen. Lines possess improved resistance to Fusarium wilt race 4 when compared to commercial cultivars. This is the first time that the United States and Uzbekistan have publicly released G. barbadense germplasm.